Adopting Maternity : White Women Who Adopt Transracially or Transnationally. - Moosnick, Nora (ABC-CLIO, 2004)
Examines issues surrounding adoption across racial and national lines and contrasts this with monoracial adoption, and provides feminist analysis of the experience of mothering adopted children.